Effect of cadmium chloride on the melanophores of Channa striatus (Bloch) - Radhakrishnan, M V; Hemalatha, S; Paul, V I (Indian Journal of Fisheries, 2011)
Sublethal effects of cadmium chloride (10 ppm. 10% of 96 h LC50) on the melanophores of Channa striatus was investigated to understand its toxicity on melanophore morphology. Observed toxicopathological alterations include statistically significant variations in the number, size and shape of the melanophors. Due to the lysis of the melanophores, the melanin contents are poured into the surrounding matrix of the connective tissue, between 20 and 30 days of exposure. The cadmium induced morphological changes in the melanophores seem to be an attempt by the organism to protect the delicate epidermis from the toxic medium. In addition to the physiological colour changes, there occurs slow morphological colour changes also as evidenced by the gradual regeneration of the chromatophores. The density of chromatophores is maximum after 45 days. The regenerated pigment cells were smaller in size and more in number when compared with the normal melanophores. The present study also shows a melanizing effect against cadmium toxicity.